2021
DOI: 10.1088/1361-6463/ac3170
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence and functionalization of solution processed high-k hybrid gate insulators for high performance oxide thin-film transistors

Abstract: We demonstrate a solution processed gate insulator (GI) with high dielectric constant (high-k) of up to ∼8.9 for high performance and low voltage operation amorphous InGaZnO (a-IGZO) thin-film transistors (TFTs). High mobilities of up to ∼30 cm2 V s−1, threshold voltage of <0.5 V, and low off current (∼10−12 A) can be achieved through the combination of high-k BaTiO x (BTO) nanoparticles and a polysiloxane (PSX) polymer matrix. This combination enables a lower process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…9 Our previous work has demonstrated that the incorporation of high-k BTO nanoparticles into a polymer to form a polymer nanocomposite is an effective gate insulator film for high performance amorphous oxide semiconductor (AOS) TFTs. 10 AOS TFTs are competent components for scalable-area electronics due to their attractive features of high mobility, low fabrication temperature, solution-process compatibility, and flexibility. 11 Numerous research has been performed to explore the potential of AOS TFT devices for various electronic purposes such as display, memory, and various sensors applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…9 Our previous work has demonstrated that the incorporation of high-k BTO nanoparticles into a polymer to form a polymer nanocomposite is an effective gate insulator film for high performance amorphous oxide semiconductor (AOS) TFTs. 10 AOS TFTs are competent components for scalable-area electronics due to their attractive features of high mobility, low fabrication temperature, solution-process compatibility, and flexibility. 11 Numerous research has been performed to explore the potential of AOS TFT devices for various electronic purposes such as display, memory, and various sensors applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the leakage current of film devices fabricated by the solution method can only reach less than 10 −6 –10 −7 A/cm 2 @ 1.0 MV/cm [ 15 , 16 ]. Therefore, the preparation of metal oxide films with excellent properties by solution method at low temperature has attracted extensive attention from researchers [ 12 , 17 , 18 , 19 ]. Solution-based manufacturing significantly reduces manufacturing costs by eliminating vacuum deposition processes and replacing them with printable precursor materials.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of film deposition technology, the recent use of solution-based processes alleviates the shortcomings of the high cost of the vacuum method which is not suitable for industrial development. Therefore, the preparation of metal oxide films with excellent properties by solution method at low temperature has attracted extensive attention of researchers [4][5] . Solution-based manufacturing significantly reduces manufacturing costs by eliminating vacuum deposition processes and replacing them with printable precursor materials.…”
mentioning
confidence: 99%